Peran Bimbingan Belajar AHE Tawangrejo dalam Meningkatkan Kemampuan Membaca Siswa Kelas Rendah - Shofria Ihda Mahayyun (Sekolah Tinggi Agama Islam Pati, 2022)
This study aims to determine the role of the AHE (Great Children) tutoring institution of Tawangrejo in improving the reading ability of low-grade students. The government through Government Regulation Number 17 in 2010 concerning Management and Implementation of Education strictly prohibits the existence of tests as a requirement for acceptance of elementary school/Islamic elementary school students. The prohibition is contained in Article 69 paragraph 5 which said,